China and global internet governance: toward an alternative analytical framework. Issue 3 (2nd July 2016) - Shen, Hong
Abstract : Drawing on historical methods, this study assesses the conventional "cyber-sovereignty" framework, which has been used to capture and interpret China's stance toward global Internet governance. This framework focuses on political control and tends to reduce China's policies to the attempts by an authoritarian state to elevate governments and intergovernmental organizations to be the only legitimate governors of global cyberspace. As it traces the evolution of China's relationship with the global Internet in the past three decades, the study demonstrates that China's stance is more complex than the prevalent framework allows and that it is both built upon and different from the US-centric, market-oriented Internet governance scheme. This study recognizes the inadequacy of the conventional framework and invokes a theory of critical political economy of communication, thereby offering an alternative model to explicate the complex power dynamics behind China's changing strategies. The alternative model advanced in this study is based on the understanding of China's evolving approach as the product of multifaceted interactions among a group of power-holders that include both state agencies and business units on the transnational level.